An evolutionary behaviorist perspective on orgasm. (1st January 2016) - Fleischman, Diana S.
Abstract : Evolutionary explanations for sexual behavior and orgasm most often posit facilitating reproduction as the primary function (i.e. greater rate of fertilization). Other reproductive benefits of sexual pleasure and orgasm such as improved bonding of parents have also been discussed but not thoroughly. Although sex is known to be highly reinforcing, behaviorist principles are rarely invoked alongside evolutionary psychology in order to account for human sexual and social behavior. In this paper, I will argue that intense sexual pleasure, especially orgasm, can be understood as a primary reinforcer shaped by evolution to reinforce behavior that facilitates reproductive success (i.e. conception through copulation). Next, I will describe an evolutionary account of social shaping. In particular, I will focus on how humans evolved to use orgasm and sexual arousal to shape the social behavior and emotional states of others through both classical and operant conditioning and through both reproductive and non-reproductive forms of sexual behavior. Finally, I will describe how orgasm is a signal of sensitivity to reinforcement that is itself reinforcing.